The distribution function of plasma particles in longi-tudinal magnetic and radial electric fields - Chibisov, D.V. (Вопросы атомной науки и техники, 2014)
The problem of determining the distribution function of particles in plasma that is produced in crossed longitudinal magnetic and radial electric fields is solved. It is assumed that the velocity probability distribution functions for the particles of the residual gas before its ionization or initial plasma before it has appeared in crossed fields are Maxwellian with non-zero thermal velocities. Then produced plasma particles are moving in crossed fields without collisions. The obtained distribution function is written in the coordinates of the guiding center. The expressions for the distribution function in the limiting cases of strong and weak electric field are also obtained. Решается задача об определении функции распределения частиц в плазме, которая создается в скрещенных продольном магнитном и радиальном электрическом полях. Предполагается, что функция распределения по скоростям частиц остаточного газа до его ионизации, или начальной плазмы, прежде чем она появляется в скрещенных полях, является максвелловской с ненулевой тепловой скоростью. Образовавшиеся частицы плазмы затем движутся в скрещенных полях без столкновений. Полученная функция распределения записана в координатах ведущего центра. Получены также выражения для функции распределения в предельных случаях сильного и слабого электрических полей. Розв’язано задачу про визначення функції розподілу частинок у плазмі, яка створюється в схрещених поздовжньому магнітному і радіальному електричному полях. Вважається, що функція розподілу за швидкостями частинок залишкового газу до його іонізації, або початкової плазми, перш ніж вона з'являлася в схрещених полях, є максвелiвською з ненульовою тепловою швидкістю. Частинки плазми, що утворилися, рухаються далі в схрещених полях без зіткнень. Здобуту функцію розподілу записано в координатах ведучого центра. Здобуто також вирази для функції розподілу в граничних випадках сильного та слабкого електричних полів.